THE SPECIFIC TOPIC FOR PREPARING PROSPECTIVE MATHEMATICS TEACHERS - DOFKOVÁ, Radka (Trends in education, 2016)
The paper is focus on analysis of one mathematical problem from the international study Teacher Education and Development Study in Mathematics (TEDS-M). This problem was chosen because of its didactics-mathematical potencial. It could be another way of appproaching in prospective mathematics teacher preparation in lessons of didactics of mathematics.
Keywords: TEDS-M; education; mathematics